Ultrananocrystalline diamond synthesis, properties, and applications - Shenderova, Olga A.; Gruen, Dieter M. (William Andrew Pub., 2006)
A unique practical reference handbook that joins the basic science of nanoscale carbon structures, particularly its diamond phase, with detailed information on nanodiamond synthesis, properties, and applications.
Keywords: Nanodiamonds -- Synthesis.; Nanodiamonds -- Analysis.; Diamond powder -- Industrial applications.; Diamond thin films -- Industrial applications.; elektronické knihy; electronic books